Syntactic Properties Of The English Verbs In The Students' Essays - H. Muhammad Basri D. (Universitas Negeri Malang, 2016)
This cross-sectional study aimed to explain the epithet of verb performance within the syntactic properties gained by the students in their essays, i.e. (1) tense, (2) aspect, (3) voice, and (4) mood. The data had been gathered from the 50 samples for each graded level by using a proportional random sampling technique. The processes of soft data attempted to search the epithet of verb performance through the equilibriums between accuracy and inaccuracy. As a result, the research findings indicated that epithet of the students' verb performance was 12.06%, including tense (27.83 %), aspect (21.51%), voice (-35.72%), and mood (34.63%).